KEWENANGAN AHLI WARIS DIREKTUR PERSEROAN KOMANDITER YANG MENINGGAL DUNIA SEBELUM JANGKA WAKTU KREDIT BERAKHIR - Tommy Leonard (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2022)
The death of a complementary partner affects debt agreement that was made by CV. For this reason, it’s necessary to study process of granting bank credit according to Law Number 10/1998, legal protection of the rights of heirs of complementary partners to inherited assets used as collateral for debt of a limited liability company and settlement of credit on behalf of a limited liability company using personal guarantees of complementary partners who have dies before the credit period ends. The type of research used is normative juridical whichis descriptive analysis. Dsata collection technique used is literature study. The process of granting bank credit according to Law Number 10/1998, namely: submitting credit applications, credit investigation and analysis, credit approval, credit agreements and credit disbursement. Legal protection of rights of heirs of complementary partners to inheritance which is used as collateral for the debt of a limited liability company is seen in two forms. If the heir rejects inheritance, then he is deemed to have never become an heir and his portion falls to the other heirs. Furthermore, if heir receives an inheritance, then the heir has responsibilities and obligations to CV as new shareholder. Therefore, CV's articles association clause is strongest legal protection that can be given to heirs. Completion of credit on behalf of limited liability company that uses personal guarantee of a complementary partner has passed away before credit period ends, management be carried out by Heritage Treasure Hall.